APPLICATION OF BIOINFORMATICS IN THE STUDY OF DIVERSITY OF THE TREE SPECIES IN MELGHAT SANCTUARY, MELGHAT TIGER RESERVE, MAHARASHTRA: Life Science-Botany - B. KALBANDE, RANJAN (International Journal of Life Science and Pharma Research, 2014)
Biodiversity stands for all living things on earth. It refers to the range of variations among a set of entities and is commonly used to describe the variety and variability of living organisms in terms of genetic diversity, species diversity and ecological diversity. In the present study, bioinformatics tools were used in the study of morphodiversity of trees using photographic collection of plants specimens along with their descriptions. The study on 1016 compartment dealt with the data collection for Vegetation-Spot potential through Google maps photographic monitoring method to evaluate the potentially important data in identification of forest land. Specimen Browser System: SBS was applied as a tool for accessing botanical specimen collections and this information was used in linking sources and destinations. It was an opportunity to apply technology that would enable us to unlock the wealth of biodiversity information that existed in the forest of Melghat.